2016
DOI: 10.1001/jamaoncol.2016.0891
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of Phosphatidylinositol-3-Kinase Pathway Alterations Across 19 784 Diverse Solid Tumors

Abstract: PI3K pathway aberrations are among the most common in cancer. They do not segregate by classic cancer histologic characteristics. Patterns of biomarker coalterations involving HER2 and hormone receptors may be important for optimizing combination treatments across cancer types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
166
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 212 publications
(173 citation statements)
references
References 70 publications
3
166
0
Order By: Relevance
“…4 The terminology "aberrant muscle syndrome" or "accessory muscle syndrome" has been suggested to describe patients with "hypertrophy of the hand and arm because of aberrant muscles with or without hypertrophy of the muscles." 1,[9][10][11] Previous studies show that the same PIK3CA hotspot mutations found in cancer are found in PROS. 6 The etiology remains still undetermined but it has recently been reported that isolated congenital muscular upper limb overgrowth can be related to somatic mosaic PIK3CA mutations.…”
Section: Introductionmentioning
confidence: 81%
“…4 The terminology "aberrant muscle syndrome" or "accessory muscle syndrome" has been suggested to describe patients with "hypertrophy of the hand and arm because of aberrant muscles with or without hypertrophy of the muscles." 1,[9][10][11] Previous studies show that the same PIK3CA hotspot mutations found in cancer are found in PROS. 6 The etiology remains still undetermined but it has recently been reported that isolated congenital muscular upper limb overgrowth can be related to somatic mosaic PIK3CA mutations.…”
Section: Introductionmentioning
confidence: 81%
“…Activation of PI3K signaling through a variety of mechanisms, including PIK3CA activating mutations or amplification, and PTEN mutation, deletion or silencing, is found in about 40% of all human cancers (1,2). Some specific tumor types, such as breast, prostate, colorectal, and endometrial cancer, as well as glioblastoma and anaplastic thyroid carcinoma, show even higher mutation rates for members of this pathway (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Some specific tumor types, such as breast, prostate, colorectal, and endometrial cancer, as well as glioblastoma and anaplastic thyroid carcinoma, show even higher mutation rates for members of this pathway (2,3). PI3K-dependent generation of phosphatidylinositol-3,4,5-triphosphate (PIP3) triggers membrane recruitment of proteins containing a PH-domain, such as the three AKT isoforms and the PDK1 kinase.…”
Section: Introductionmentioning
confidence: 99%
“…[116][117][118][119] Comprehensive atomic-scale simulations were able to unveil the mechanisms of some oncogenic mutations. [116][117][118][119] Comprehensive atomic-scale simulations were able to unveil the mechanisms of some oncogenic mutations.…”
Section: Autoinhibition Is a Common Target Of Allosteric Driver Mutmentioning
confidence: 99%